Cathodal Transcranial Direct Current Stimulation on the Right Temporo-Parietal Junction Modulates the Use of Mitigating Circumstances during Moral Judgments - Leloup, Laëtitia; Miletich, Diana Dongo; Andriet, Gaëlle; Vandermeeren, Yves; Samson, Dana (Frontiers in Human Neuroscience, 2016)
Recently, a few transcranial magnetic stimulation (TMS) or transcranial direct current stimulation (tDCS) studies have shown that the right temporo-parietal junction (rTPJ) plays a causal role in moral reasoning especially in cases of accidental harms or failed attempted harms. The profile of results across studies is however not entirely consistent: sometimes the stimulation affects predominantly failed attempted harms while sometimes the stimulation affects predominantly accidental harms. We argue that such discrepancy could reflect different functional contributions of the rTPJ in moral judgments and that the chosen design parameters or stimulation method may differentially bring to light one or the other functional role of the rTPJ. In the current study, we found that tDCS specifically affected accidental harms but not failed attempted harms. Low cathodal stimulation of the rTPJ led to a marginally significant increase in the severity of judgments of accidental harms (Experiment 1) while higher cathodal current intensity led to a highly significant decrease in the severity of judgments of accidental harms (Experiment 2). Our pattern of results in the context of our experimental design can best be explained by a causal role of the rTPJ in processing the mitigating circumstances which reduce a protagonist’s moral responsibility. We discuss these results in relation to the idea that the rTPJ may play multiple roles in moral cognition and in relation to methodological aspects related to the use of tDCS.